Scaling the processes of human resources management of the organisation in the conditions of digital transformation - A. L. Denisova; A. S. Bunkin (Вестник университета)
In the context of the digital transformation of the economy, the processes of managing the human resources of an organisation are of particular importance as the basis for achieving operational efficiency in a highly dynamic business environment. At the same time, the existing practice of human resource management in organisations shows that the human resources management system in the context of digital transformation requires special attention from the standpoint of scaling. This paper discusses the issues of scaling the processes of managing the human resources of an organisation in the context of digital transformation, the analysis and accounting of which will increase, on the one hand, the efficiency of the organisation, on the other hand, the motivation and involvement of employees in the work process. The research paper pays special attention to the Program for the training of management personnel for organisations of the national economy of the Russian Federation from the standpoint of scaling the processes of managing the human resources of an organisation in the context of digital transformation. Systematic studies of the scaling of the organization’s human resources management processes in the view of digital transformation will determine both new approaches and technologies for human resources management and the processes of changing the organisation’s business models.